2008
DOI: 10.1007/s10457-008-9173-y
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning from wild collection to forest cultivation of indigenous medicinal forest plants in eastern North America is constrained by lack of profitability

Abstract: The forest flora of eastern North America includes many herbaceous plant species traded in domestic and international medicinal markets. Conservation concerns surrounding wild-collection exist and transitioning to cultivation in agroforestry systems has potential economic and ecological benefits. Costs and revenues associated with adopting forest cultivation were modeled for eight North American medicinal forest plants. Sensitivity analysis examined profit potential in relation to (1) discount rates; (2) propa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 16 publications
0
41
0
Order By: Relevance
“…[19] The site of attachment of the fucose residue was evident from the downfield shift of C-24 from d = 79. 6 [21] although the d-enantiomer is more commonly reported in steroidal and triterpenoid saponins, for example, in surculosides A-C from Dracaena surculosa. [22] The structure of 2 was therefore established as 3-O-…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] The site of attachment of the fucose residue was evident from the downfield shift of C-24 from d = 79. 6 [21] although the d-enantiomer is more commonly reported in steroidal and triterpenoid saponins, for example, in surculosides A-C from Dracaena surculosa. [22] The structure of 2 was therefore established as 3-O-…”
Section: Resultsmentioning
confidence: 99%
“…Over the period 1997-2005, the trade volume of C. luteum in the USA alone was approximately 9800-14 300 kg dry weight of plant material. [6] Significantly, its use is rapidly increasing, with 2001 consumption being 37 % greater than that in 2000 and 250 % of that in 1997. [7] C. luteum is currently listed by the United States Department of Agriculture (USDA) as endangered or threatened in a number of states, [4] and wild harvesting of C. luteum plants for medicinal use (wildcrafting) is thought to further threaten populations of the species.…”
Section: Introductionmentioning
confidence: 99%
“…More research is needed to evaluate the economic feasibility of this type of system; however, a study by Burkhart and Jacobson (2009) found that growing herbaceous NTFPs under natural forest canopies was not economically viable, except for ginseng ( Panax quinquefolius ) and goldenseal ( Hydrastis canadensis ). Economic feasibility would depend on an assessment of the long-term productivity of these plants on the transplantation sites, as well as the initial costs of the plant material.…”
Section: Discussionmentioning
confidence: 99%
“…Several understory species, including white trillium ( Trillium grandiflorum ), wild ginger ( Asarum canadense ), and bloodroot ( Sanguinaria canadensis ), are already listed as vulnerable in Quebec, due to risks of overexploitation of wild populations (MDDEP 2010). Their cultivation in plantation understories as non-timber forest products (NTFPs) could provide a sustainable supply of these plants, as well as an additional and earlier return on investment for plantation owners (but see findings of Burkhart and Jacobson 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Although goldenseal can be grown using field-based cultivation under artificial shade, cultivating the plant using forest-based farming approaches (i.e., agroforestry) has potential advantages over field based cultivation. These include cost savings associated with artificial shade structures (goldenseal is shade obligate) and possible reduction in disease, a higher incidence of which can be associated with field grown production (Sinclair and Catling, 1996;Burkhart and Jacobson, 2009). In a study of woodland owners in Pennsylvania, just over a third (36%) of respondents were interested in using agroforestry for specialty crop production, including forest farming of medicinal plants (Strong and Jacobson, 2006).…”
Section: Introductionmentioning
confidence: 99%